Automated tooth crown design with optimized shape and biomechanics properties - Jin, Xiaoxian; Wang, Shengfa; Hu, Jiangbei; Xu, Xiaowei; Shi, Yongji; Yu, Haishi; Wang, Jinwu; Li, Kang; Cheng, Xiaomin; Shao, Moyu; Wang, Hongkai (Frontiers in Bioengineering and Biotechnology, 2023)
Despite the large demand for dental restoration each year, the design of crown restorations is mainly performed via manual software operation, which is tedious and subjective. Moreover, the current design process lacks biomechanics optimization, leading to localized stress concentration and reduced working life. To tackle these challenges, we develop a fully automated algorithm for crown restoration based on deformable model fitting and biomechanical optimization. From a library of dental oral scans, a conditional shape model (CSM) is constructed to represent the inter-teeth shape correlation. By matching the CSM to the patient's oral scan, the optimal crown shape is estimated to coincide with the surrounding teeth. Next, the crown is seamlessly integrated into the finish line of preparation via a surface warping step. Finally, porous internal supporting structures of the crown are generated to avoid excessive localized stresses. This algorithm is validated on clinical oral scan data and achieved less than 2 mm mean surface distance as compared to the manual designs of experienced human operators. The mechanical simulation was conducted to prove that the internal supporting structures lead to uniform stress distribution all over the model.